2011
DOI: 10.1016/j.bbamem.2010.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Conformational plasticity of the influenza A M2 transmembrane helix in lipid bilayers under varying pH, drug binding, and membrane thickness

Abstract: Membrane proteins change their conformations to respond to environmental cues, thus conformational plasticity is important for function. The influenza A M2 protein forms an acid-activated proton channel important for the virus lifecycle. Here we have used solid-state NMR spectroscopy to examine the conformational plasticity of membrane-bound transmembrane domain of M2 (M2TM). 13C and 15N chemical shifts indicate coupled conformational changes of several pore-facing residues due to changes in bilayer thickness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
133
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(146 citation statements)
references
References 62 publications
(102 reference statements)
12
133
1
Order By: Relevance
“…This conformational transition provides a pathway for proton transfer past the Trp41 gate into the viral interior. In NMR studies at low pH, both conformations are observed in equilibrium with one another (40,43,44 (Fig. S1, Bottom).…”
Section: Significancementioning
confidence: 98%
See 1 more Smart Citation
“…This conformational transition provides a pathway for proton transfer past the Trp41 gate into the viral interior. In NMR studies at low pH, both conformations are observed in equilibrium with one another (40,43,44 (Fig. S1, Bottom).…”
Section: Significancementioning
confidence: 98%
“…The Inward closed state has also been characterized by solution NMR (39,40) and solid-state NMR (41,42) studies under high pH conditions. The Inward closed conformation can transition to the Inward open conformation by straightening a kink in the TM helix near Gly34 (40,43,44). This conformational transition provides a pathway for proton transfer past the Trp41 gate into the viral interior.…”
Section: Significancementioning
confidence: 99%
“…1) with tight packing of His37 and Trp41 (10,19,23,26). At lower pH the channel is more dynamic (26)(27)(28), which has precluded structure determination by solution or SSNMR. However, a series of crystallographic structures of the C open states ( Fig.…”
Section: Significancementioning
confidence: 99%
“…Higher membrane fluidity and negatively charged lipids favor H37 protonation [3133]. Cholesterol promotes the α-helical conformation [34], immobilizes tetramer rotational diffusion [35], and stabilizes tetramer assembly [36, 37].…”
Section: Introductionmentioning
confidence: 99%